PREVALENCE OF DRUG RESISTANCE AND VIRULENCE FEATURES IN Salmonella spp. ISOLATED FROM FOODS ASSOCIATED OR NOT WITH SALMONELLOSIS IN BRAZIL - Rowlands, Ruth Estela Gravato; Ristori, Christiane Asturiano; Ikuno, Alice A.; Barbosa, Maria Luisa; Jakabi, Miyoko; Franco, Bernadette Dora Gombossy de Melo (Revista do Instituto de Medicina Tropical de São Paulo, 2014)
Salmonella is the most common etiological agent of cases and outbreaks of foodborne diarrheal illnesses. The emergence and spread of Salmonella spp., which has become multi-drug resistant and potentially more pathogenic, have increased the concern with this pathogen. In this study, 237 Salmonella spp., associated or not with foodborne salmonellosis in Brazil, belonging mainly to serotype Enteritidis, were tested for antimicrobial susceptibility and the presence of the virulence genes spvC, invA, sefA and pefA. Of the isolates, 46.8% were sensitive to all antimicrobials and 51.9% were resistant to at least one antimicrobial agent. Resistance to more than one antimicrobial agent was observed in 10.5% of the strains. The highest rates of resistance were observed for streptomycin (35.9%) and nalidixic acid (16.9%). No strain was resistant to cefoxitin, cephalothin, cefotaxime, amikacin, ciprofloxacin and imipenem. The invA gene was detected in all strains. Genes spvC and pefA were found in 48.1% and 44.3% of strains, respectively. The gene sefA was detected in 31.6% of the strains and only among S. Enteritidis. Resistance and virulence determinants were detected in Salmonella strains belonging to several serotypes. The high rates of antibiotic-resistance in strains isolated from poultry products demonstrate the potential risk associated with the consumption of these products and the need to ensure good food hygiene practices from farm to table to reduce the spread of pathogens relevant to public health.